Analyses of human papillomavirus genotypes in cervical cancer patients using real-time PCR (Annals of Medical Research, 2026)
Aim: The aim of this study was to identify the most prevalent Human Papillomavirus (HPV) genotypes associated with cervical cancer in Gaziantep and to determine the most appropriate HPV vaccine for individuals who have not yet been infected.Materials and Methods: This retrospective cross-sectional study included 74 patients diagnosed with cervical cancer at Gaziantep University Faculty of Medicine between December 2005 and June 2019. Formalin-fixed paraffin-embedded tissue samples were retrieved from the pathology archives. HPV DNA was extracted and genotyping of 14 high-risk HPV types was carried out by real-time PCR.Results: All patients were histopathologically diagnosed with squamous cell carcinoma. Single HPV type infection was detected in six patients (8.2%) (HPV 16 in five, HPV 56 in one), whereas multiple infections were observed in 68 patients (91.8%). Among these, HPV 16 was identified in 100% of cases, HPV 45 in 82%, HPV 18 in 45%, HPV 56 in 19%, and HPV 33 in 16%. Overall, HPV 16, 45, and 18 genotypes emerged as the most frequent types contributing to cervical cancer in this region.Conclusion: Given the genotypes identified in this study, the nonavalent HPV vaccine (9-valent; HPV types 6, 11, 16, 18, 31, 33, 45, 52, and 58) appears to be the most suitable option for our population. However, due to its limited availability in Turkey, the quadrivalent HPV vaccine (4-valent; HPV types 6, 11, 16, and 18), which may provide partial cross-protection against HPV 45, could serve as a reasonable alternative.
Keywords: Human papillomavirus; HPV vaccine; Cervical cancer; Genotype; Real-time PCR